Targeting the GRP78 Pathway for Cancer Therapy - Lu, Guanhua; Luo, Hui; Zhu, Xiao (Frontiers in Medicine, 2020)
The 78 kDa glucose-regulated protein (GRP78) plays an important part in maintaining protein stability, regulating protein folding and inducing apoptosis autophagy, which is considered as a powerful protein. Meanwhile, it also plays a role in ensuring the normal function of organs. In recent years, more and more researches have been carried out on the targeted therapy of GRP78, mainly focusing on its relevant role in tumor and its role as a major modulator and modulator of subordinate pathways. The ability of GRP78 to respond to endoplasmic reticulum stress (ERS) determines whether tumor cells survive, the changes in expression level of GRP78 regulated by endoplasmic reticulum (ER) caused by various factors will directly or indirectly affect cell proliferation, apoptosis and injury, or reduce the body's defense ability, or have protective effects on various organs.